Bone deep - White, Randy Wayne (White, Randy Wayne. Doc Ford series, 2014)
When a Crow Indian acquaintance of Tomlinson's asks him to help recover a relic stolen from his tribe, Doc Ford is happy to tag along--but neither Doc nor Tomlinson realize what they've let themselves in for. Their search takes them to the part of Central Florida known as Bone Valley, famous primarily for two things: a ruthless subculture of black-marketers who trade in illegal artifacts and fossils, and a multibillion-dollar phosphate industry whose strip mines compromise the very ground they walk on. Neither enterprise tolerates nosy outsiders. For each, public exposure equals big financial losses--and in a region built on a million-year accumulation of bones, there is no shortage of spots in which to hide a corpse. Or two"--